Back on track - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The island of Dominica in the Caribbean is constructing a new irrigation infrastructure for its banana sector. The t 16 million programme, like other EU-backed initiatives on the banana-producing Windward Islands, aims to reduce the impact of...